2014
DOI: 10.1149/2.016406jss
|View full text |Cite
|
Sign up to set email alerts
|

High Rate Chemical Mechanical Polishing of Boron-Doped Polycrystalline Silicon

Abstract: In this paper, the effect of lubrication on the polish rate and the surface quality of highly boron-doped polysilicon is presented. The mechanical effects of polishing were studied by altering the CMP process and lubrication regime. It was shown that increasing the polish velocity and slurry flow rate does not always increase the polish rate and that the lubrication behavior plays a dominant role in this process. Increasing the mechanical forces and altering the lubrication regime to boundary and dry lubricati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…This carrier concentration is ∼70% higher than the concentration in the samples in our prior work (Pirayesh and Cadien, 2014) and the polish rate is expected to be lower. As mentioned earlier, since the amount of material that has to be polished is >10 m, improving the polish rate is critical for throughput and manufacturability.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…This carrier concentration is ∼70% higher than the concentration in the samples in our prior work (Pirayesh and Cadien, 2014) and the polish rate is expected to be lower. As mentioned earlier, since the amount of material that has to be polished is >10 m, improving the polish rate is critical for throughput and manufacturability.…”
Section: Resultsmentioning
confidence: 58%
“…The curve has two regimes, between 80 and 90 rpm the COF increases rapidly, while at 100 rpm and above the COF increases slowly. In the boundary lubrication regime, it is expected that the COF would decrease with increasing velocity (Pirayesh and Cadien, 2014). This indicates that at low flow rates the polish is not in the boundary lubrication regime.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Enhancement of polish rate can be achieved by optimizing the polish properties such as pressure, flow rate and velocity, as has been shown in our prior publications. 10,11 Polish rate can also be improved by enhancing the slurry chemistry and by understanding the basic properties of the slurry.Pietsch et al studied the influence of slurry pH and found that the maximum etch and polish rate of single crystal silicon (n-type Si (100) and (111) wafers with 150 cm resistivity) occurs at pH∼11. 8,[12][13][14] They showed that the presence of hydroxyl anions plays a major role in the chemical etching of the polysilicon surface since OH − anions weaken the Si-Si bonds by acting as a strong polarizer.…”
mentioning
confidence: 99%